Dose-dependent impact of tixagevimab–cilgavimab as primary prevention against SARS-CoV-2 in immunocompromised individuals - Daniela Dluzynski; Paddy Ssentongo; Cory M. Hale; Shareef K. Shaheen; Natella Maglakelidze; Jeffrey M. Sivik; Maria Paula Henao; Vernon M. Chinchilli; Catharine I. Paules (Scientific Reports)
Abstract Tixagevimab–cilgavimab was available for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) prevention from December 2021 to January 2023, with dosing changes to reflect circulating variants. In a retrospective analysis of 597 immunocompromised individuals, incidence of SARS-CoV-2 infection was compared between those who did and did not receive tixagevimab–cilgavimab. A proportional hazards regression model with a time-dependent regressor for tixagevimab–cilgavimab dose was applied to assess cumulative doses. Secondary analyses were performed in hematopoietic stem cell transplant (HSCT) and chimeric antigen receptor (CAR)-T cell therapy recipients. There was no difference in SARS-CoV-2 infections between tixagevimab–cilgavimab recipients and controls (p = 0.27). There was a trend towards protection with increasing dose from 150 (HR 0.83, CI 0.50–1.38) to 600 mg (HR 0.48, CI 0.06–3.63) when truncating data on November 1st, 2022, which was also seen in HSCT or CAR-T cell therapy recipients, 150 mg (HR 0.71, CI 0.31–1.65) to 600 mg (HR 0.26, CI 0.01–7.47). This was most evident in immunocompromised individuals when variants neutralized by tixagevimab–cilgavimab in vitro were circulating; effectiveness 74%. Supports a proof of concept for monoclonal antibodies in immunocompromised individuals as a prevention strategy against novel viruses.